SINTESIS DAN KARAKTERISASI MATERIAL SILIKA MESOPORI SBA-15 DENGAN ULTRASONIC ASSISTED SOL-GEL METHOD MENGGUNAKAN PELARUT ASAM ASETAT - Siti Sarah; RR Dirgarini Julia Nurlianti Subagyono; Veliyana Londong Allo (PROSIDING SEMINAR KIMIA, 2022)
Synthesis and characterization of mesoporous silica material SBA-15 with ultrasonic assisted sol-gel method using acetic acid solvent has been conducted. The mesoporous silica material SBA-15 was characterized by N2 adsorption/desorption Analysis, Small Angle X-Ray Diffraction (SAXRD), Scanning Electron Microscopy (SEM), Fourier Transform Infrared (FTIR). SBA-15 material resulted from the calcination method for template removal has a surface of 876 m2/g, a pore volume of 5,1 cm3/g and a pore diameter of 1,13 nm. The SAXRD pattern of SBA-15 showed three distinctive peaks with Miller indeces of 100, 110 and 200 respectively. The morphology of the SBA-15 material has the form of aggregate particles with a reguler cylindrical structure on the particles. Infrared spectra of SBA-15 showed the presence of functional groups, namely Si-O-Si, Si-OH and –OH. Keywords: Mesoporous silica, SBA-15, sonication